Representing emotive meaning in visual images: A social semiotic approach - Feng, D.; O'Halloran, Kay (Elsevier BV, 2012)
This study examines how emotive meaning is represented in visual images using the semiotic resources of facial expression, touch and body orientation. Complementing the cognitive metaphorical interpretation, the visually represented emotive behaviors are theorized as partial iconic representations of real life behaviors, which are in turn indexes of emotion. Adopting a social semiotic approach, this paper formulates facial expression, touch, and body orientation as inter-related systems of meaning, the selection and combination of which constitutes a systemic functional “lexico-grammar” for analyzing and interpreting meaning making in visual imagery. The systems are then used to explain how emotive meanings are represented in comic books. The analysis shows that cartoonists’ systemic choices for representing emotions are largely consistent with the coding accuracy of facial behaviors on the one hand, and style guidelines advocated in comic handbooks on the other. Through the examination of both American and Japanese comics, it is demonstrated that the social semiotic lexico-grammatical approach is not only effective in explaining the emotion resources in nonverbal behavior, but also useful for investigating cultural differences in the visual depiction of emotion. The systemic choices also provide artists with a framework to “design” emotion in creative visual media such as comics, and possibly in computer vision, game design and related domains.